Performance of Chickpea (Cicer arietinum) Frontline demonstrations in Rajasthan - PRASAD, DASHARATH; PRAKASH, VIJAY; MEENA, R S; BAIRWA, S K (The Indian Journal of Agricultural Sciences, 2022)
Chickpea (Cicer arietinum L.) is the most important rabi pulse crop of Rajasthan. The intervention of chickpea frontline demonstrations (FLDs) is one of the best ways to educate the conventional cultivators about productivity potential and profitability. The present study was carried out to determine the economic viability of technology transfer and adoption of chickpea in semi-arid region of North-West plain (NWP) zone of Rajasthan. Frontline demonstrations were conducted at Agricultural Research Station, S K Rajasthan Agricultural University, Bikaner, Sriganganagar, Rajasthan, to enhance chickpea production and improve livelihood of small and marginal farmers. Total 260 demonstrations were conducted under 65 ha area in different villages of Sriganganagar district of Rajasthan during rabi season of 2012–13 to 2019–20. The seed of newly released chickpea varieties, viz. GNG-1581, GNG-1958, GNG-2144 and GNG-2171 were provided with other production and protection inputs. Results of the study revealed that the package and practices improved the seed yield of chickpea by 17.2%. The annual increase in the yield in different seasons ranged from 12.4% to 23.4%. The average technology gap (6.6 q/ha) and average extension gap (2.5 q/ha) suggested further improvement in the extension activities. The average benefit : cost ratio was significantly higher (2.81) under demonstrated plot as compared to farmers’ practice (2.48). Economic studies of individual years over eight years indicated that adoption of improved practices fetched more profit compared to farmers’ practices.